Radionuclide Imaging of Viable Myocardium: Is it Underutilized? - Mylonas, Ilias (Current Science Inc., 2011)
Coronary artery disease is the major cause of heart failure in North America. Viability assessment is important as it aims to identify patients who stand to benefit from coronary revascularization. Radionuclide modalities currently used in the assessment of viability include (201)Tl SPECT, (99m)Tc-based SPECT imaging, and (18)F-fluorodexoyglucose ((18)F-FDG)-PET imaging. Different advances have been made in the last year to improve the sensitivity and specificity of these modalities. In addition, the optimum amount of viable (yet dysfunctional) myocardium is important to identify in patients, as a risk–benefit ratio must be considered. Patients with predominantly viable/hibernating myocardium can benefit from revascularization from a mortality and morbidity standpoint. However, in patients with minimal viability (predominantly scarred myocardium), revascularization risk may certainly be too high to justify revascularization without expected benefit. Understanding different radionuclide modalities and new developments in the assessment of viability in ischemic heart failure patients is the focus of this discussion.